The travel diaries of Albert Einstein : South America, 1925 - Einstein, Albert, 1879-1955 (Princeton University Press, 2023)
"A popular edition of Albert Einstein's travel diaries and related writings from his 1925 visit to South America"-- Provided by publisher.
Keywords: Einstein, Albert, -- 1879-1955 -- Diaries.; Einstein, Albert, -- 1879-1955 -- Travel -- South America.; Einstein, Albert, -- 1879-1955 -- Correspondence.; Einstein, Albert, -- 1879-1955; South America -- Description and travel.; Amérique du Sud -- Descriptions et voyages.; SCIENCE / History.; BIOGRAPHY & AUTOBIOGRAPHY / Science & Technology.; Travel; South America; 1922-1923.; Albert Einstein.; Argentina.; Brazil.; Buenos Aires.; Einstein enthuses about the stunning vistas of lush vegetation in Rio de Janeiro.; Einstein the person.; Einstein wrote in journal.; Einstein's diary.; Einstein's journal.; Einstein's musings on science.; Princeton University press.; South America travel diary.; South America, 1925.; Spain.; Supplementary materials.; The Travel Diaries of Albert Einstein.; Uruguay.; Ze'ev Rosenkranz.; a bibliography.; admiration for the Uruguayans.; an index.; art.; biography.; books about Albert Einstein.; chronology.; editorial annotations.; humanitarian icon.; letters.; long ocean voyages.; meetings with other prominent colleagues and statesmen.; numerous illustrations.; philosophy.; politics.; postcards.; preeminent scientist.; speeches.; statements.; telegraphic-style diary entries.; the inner thoughts of Einstein.; the life of Albert Einstein.; three month journey.; Electronic books.; Diaries; Personal correspondence